The connection between academic achievements and market demand: The role and practice of technology and innovation in knowledge transfer - RUAN, Jinhua; ZHANG, Weina; Hu, Ziping (Edelweiss Applied Science and Technology, 2024)
With the advancement of science, technology, and innovation, the mechanism for transforming academic research into commercially viable solutions has become a key area. This study aims to explore how science, technology, and innovation can collaborate to promote the commercialization of academic achievements, and to reveal their roles and obstacles in this process. Through case analysis of stakeholders such as academia, business, and technology transfer offices, combined with semi-structured interviews and non participatory observations, this study delves into the main mechanisms of knowledge transfer, how innovation drives this process, and the challenges that exist. Research has found that knowledge transfer is achieved through three mechanisms: formal collaboration, informal networks and open innovation, as well as knowledge absorption and adaptation. In addition, technological innovation, especially artificial intelligence, data analysis, and blockchain technology, has become a catalyst for accelerating the transformation of academic research into commercial applications. However, the inconsistency of expectations between academia and business and intellectual property issues remain the main obstacles in knowledge transfer. This study provides a theoretical basis for cooperation between academia and industry, and offers practical suggestions for improving knowledge transfer mechanisms.